(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To compare the degree of liver fibrosis assessed by Fibroscan in patients with alcoholic fatty liver disease (AFLD) and non-alcoholic fatty liver disease (NAFLD). Subjects and Methods: This prospective cross-sectional study included 152 patients with NAFLD and 152 patients with AFLD who were examined and treated at at the Department of Examination and Treatment on Demand, Bach Mai Hospital from March 2024 to June 2024. Results: Compared with the AFLD group, the NAFLD group had a higher proportion of females (58.6%), physically inactive patients (79.6%), obesity (43.4%), diabetes mellitus (34.9%), hypertension (25.0%), and an AST/ALT ratio ≤ 1 (71.7%), with statistically significant differences (p < 0.05). The prevalence of elevated AST, ALT, and GGT levels in the NAFLD group (23.7%, 40.8%, and 37.8%, respectively) was lower than that in the AFLD group (35.5%, 46.1%, and 73.5%, respectively); differences in AST and GGT were statistically significant. Patients with AFLD showed significantly higher proportions of advanced fibrosis stages (F2, F3, and F4), higher mean liver stiffness values, and a higher prevalence of significant fibrosis compared with patients with NAFLD (31.6%, 21.1%, 11.2%; 11.1 ± 10.3 kPa; and 63.9%, respectively; p < 0.05). Significant differences between mild fibrosis (F0–F1) and significant fibrosis (F2–F4) were observed in both NAFLD and AFLD groups among patients aged over 50 years, females, non-smokers, physically inactive individuals, and patients obesity, diabetes mellitus, or hypertension (p < 0.05). A positive correlation was found between Fibroscan liver stiffness measurements and non-invasive fibrosis scores, including APRI (r = 0.66) and FIB-4 (r = 0.69). Conclusion: AFLD is associated with more severe liver injury and more advanced liver fibrosis on Fibroscan than NAFLD. NAFLD is more prevalent among females and is commonly associated with physical inactivity, obesity, hypertension, and diabetes mellitus.